2019
DOI: 10.1371/journal.pmed.1002841
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single and integrated water, sanitation, handwashing, and nutrition interventions on child soil-transmitted helminth and Giardia infections: A cluster-randomized controlled trial in rural Kenya

Abstract: Background Helminth and protozoan infections affect more than 1 billion children globally. Improving water quality, sanitation, handwashing, and nutrition could be more sustainable control strategies for parasite infections than mass drug administration, while providing other quality of life benefits. Methods and findings We enrolled geographic clusters of pregnant women in rural western Kenya into a cluster-randomized controlled trial (ClinicalTrials.gov NCT01704105) t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 50 publications
3
65
1
6
Order By: Relevance
“…The combined WASH and water chlorination interventions reduced Ascaris infection by 18-22% but 18% of children who received the WASH interventions were still infected with Ascaris. 51 None of the WASH interventions reduced…”
Section: Table: Effect Of Intervention On Diarrhoea For Randomised Comentioning
confidence: 97%
See 1 more Smart Citation
“…The combined WASH and water chlorination interventions reduced Ascaris infection by 18-22% but 18% of children who received the WASH interventions were still infected with Ascaris. 51 None of the WASH interventions reduced…”
Section: Table: Effect Of Intervention On Diarrhoea For Randomised Comentioning
confidence: 97%
“…Finally, 39% of mothers reported that their child had consumed soil in the previous week. 51 In the SHINE trial in Zimbabwe, the WASH intervention reduced maternal-reported child geophagia by 63% but 27% of children in the WASH group still ingested faecalcontaminated soil. The WASH inter vention had a very small effect on total parasite infections but had no effect on carriage of bacterial or viral enteropathogens using molecular diagnostics.…”
Section: Health Policymentioning
confidence: 99%
“…More than 550 million school children live in areas where intestinal parasitic infections (IPI) are endemic with 450 million of the illnesses occurring in sub-Saharan Africa (2,(4)(5)(6)(7). Parasitic infections are among the most preventable neglected tropical infections in humans (8).…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted among households enrolled in a large-scale randomized controlled trial of water, sanitation, handwashing, and nutrition interventions in rural Kenya (WASH Benefits Kenya). The trial found that the water intervention (chlorination) improved microbial water quality as measured by E. coli, but none of the interventions reduced E. coli contamination on child hands or on sentinel toy balls [38], and none of the interventions reduced child diarrhea or improved child growth [39]. The study investigators concluded that the interventions were not able to sufficiently reduce fecal contamination in the household environment [40]; one potential explanation is that animal feces were a substantial source of fecal contamination in study households [38].…”
Section: Introductionmentioning
confidence: 99%